Clearfil Protect Bond™ versus Uni-Etch™ antibacterial self-etchant: A war of giants against shear bond strength - Harish Atram; Sanjeev V Jakati; Mrunal Aley; Achint Chachada; Mugdha Mankar (Wolters Kluwer Medknow Publications, 2016)
Aims and Objectives: To use antibacterial agents with two conventional bonding systems and evaluate the shear bond strength (SBS) of bracket to enamel. Materials and Methods: Overall, 120 human-extracted first premolars were used. The specimens were equally divided into six sub-groups of 20 samples. Control groups were bonded with Transbond XT™ light cure (Group I, after etching with 37% phosphoric acid, 3M Unitek™ ) and Unite™ self-cure adhesive (Group II, after etching with 37% phosphoric acid, 3M Unitek™ ). Experimental groups included teeth surface first coated with Clearfil Protect Bond™ (Kuraray, Osaka, Japan) (and then bonded with Transbond XT™ [Group III] or Unite™ [Group IV]) or bonded with Uni-Etch™ antibacterial self-etchant (and then bonded with Transbond XT™ [Group V] or Unite™ [Group VI]). The third generation MBT bracket bonding system with 0.022 slots was used for bonding. All specimens were tested on Instron machine 5567 (SIES Institute of packaging, Nerul, Navi Mumbai, India) to evaluate the SBS. The sheared surfaces were also investigated with a stereomicroscope to assess adhesive remnants index (ARI scores) on the specimen surfaces. Results: Mean SBS in Group I-Group VI was 10.53 (2.91), 9.12 (2.56), 9.86 (1.98), 6.96 (2.92), 9.57 (2.02), and 7.65 (2.34) megapascals, respectively. Significant differences were only seen between Group III and IV and between Group II and IV. With respect to ARI scores, significant differences were seen only for comparison between Groups II, IV, and VI. Conclusion: Newly developed antibacterial agent could be used with conventional bonding systems effectively to decrease white spots; when used with Transbond XT™ light cure, the original SBS did not get affected, but when used with Unite™ self-cure bonding system, it led to reduced SBS significantly.